1989
DOI: 10.1111/j.1532-5415.1989.tb05499.x
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing of Psychotropics in Elderly Nursing Home Patients

Abstract: This study examined the prescribing of psychotropic drugs for patients 65 years of age and older in nursing homes using data from the 1984 National Nursing Home Survey pretest. The most frequently used antipsychotic, anxiolytic, antidepressant, and sedative/hypnotic medications were respectively: haloperidol, hydroxyzine, doxepin, and temazepam. Results indicate that more than one-fifth of the patients having orders for psychotropic medications did not have a documented mental disorder. More than one-fourth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
1
1

Year Published

1989
1989
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(62 citation statements)
references
References 15 publications
(18 reference statements)
4
56
1
1
Order By: Relevance
“…Beardsley et al (1989) found in a US study of 526 nursing home residents that out of 182 residents receiving psychotropic medication, 21% did not have a psychiatric or organic brain disorder, possibly explained by poor documentation of illness. Garrard et al (1991) con®rmed that in nursing homes, the documentation of reasons for prescribing neuroleptic drugs is poor.…”
Section: Documentationmentioning
confidence: 94%
“…Beardsley et al (1989) found in a US study of 526 nursing home residents that out of 182 residents receiving psychotropic medication, 21% did not have a psychiatric or organic brain disorder, possibly explained by poor documentation of illness. Garrard et al (1991) con®rmed that in nursing homes, the documentation of reasons for prescribing neuroleptic drugs is poor.…”
Section: Documentationmentioning
confidence: 94%
“…Reports about the less than optimal prescription and misuse of these drugs in the elderly, particularly in institutions, have been matters of growing concern (Beardsley et al, 1989;Rovner et al, 1990;Spore et al, 1996). Their use, while effective in controlling psychotic symptoms and behavioral disturbances, is complicated by the age-related changes in the brain and other body organs and the presence of psychiatric and physical comorbidities (Schneider, 1993;Catterson et al, 1997).…”
Section: Introductionmentioning
confidence: 97%
“…With the sizeable literature on psychotropic drug use in the elderly, a dearth of information still exists in this group. In addition, these studies were conducted mostly in speci®c settings; at nursing homes and board-and-care facilities (Beardsley et al, 1989;Rovner et al, 1990;Spore et al, 1996). This study therefore presents a populationbased survey of psychotropic drug use in the very old.…”
Section: Introductionmentioning
confidence: 99%
“…There is little other published data on the speci®c drug use of long acting benzodiazepines by the community dwelling elderly in Ireland or the United Kingdom, for comparative purposes. However, North American data from 1985 showed that one third of elderly benzodiazepine users were receiving long half-life drugs (Ray et al, 1989), and nursing home data reported a similar ®gure (Beardsley et al, 1989). Therefore, the proportion of elderly benzodiazepine users in Dublin on long acting agents, and consequently exposed to potentially serious side eects, is high, especially in view of the increasing availability of short acting benzodiazepines in recent years.…”
Section: Discussionmentioning
confidence: 95%